Diagnosing literary genius a cultural history of psychiatry in Russia, 1880 - 1930 - Sirotkina, Irina E. 1963- (Johns Hopkins Univ. Press, 2002)
Irina Sirotkina explores the transformations of Russian psychiatric practice through its relationship to literature during the period 1880-1930, when psychiatrists began to view literature as an indicator of the nation's mental health.
Keywords: Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1880-1917; Geschichte 1917-1930; Psychiatry - History - Russia - 19th century; Psychiatry - History - Russia - 20th century; Psykiatri - historia - Ryssland - 1800-talet - 1900-talet; Russian literature - History and criticism - 19th century; Russian literature - History and criticism - 20th century; Rysk litteratur - 1800-talet - 1900-talet; Geschichte; Psychiatry -- Russia -- History -- 19th century; Psychiatry -- Russia -- History -- 20th century; Russian literature -- 19th century -- History and criticism; Russian literature -- 20th century -- History and criticism; Psychiatrie; Russland; Sowjetunion